Decoding Brugada syndrome: A comprehensive analysis of pathophysiology, genetic foundations and advanced clinical management - Aman Kumar; Junaid Tantray; Sourabh Kosey; Chingtham Henthoibi Devi; Bhupendra Prajapati (Health Sciences Review, 2025)
Background: Sudden cardiac death is linked to the hereditary condition known as Brugada syndrome (BrS), an autosomal dominant heart illness. Another name for it is sudden nocturnal death syndrome, a novel arrhythmogenic condition that has drawn attention because of its intricate pathophysiology and potential medical applications. BrS is generally considered a fairly uncommon condition, with an estimated 0.05 % global frequency and 0.4 % pattern. The reported prevalence of BrS ranges from 1 in 2000 to 1 in 5000. Objective: This study seeks to provide a complete understanding of the pathophysiology, genetic basis, diagnostic criteria, and treatment methods related to Brugada syndrome. Methods: A narrative synthesis of current research was undertaken, concentrating on epidemiology, electrophysiological processes, genetic alterations (specifically SCN5A), and clinical management techniques, including risk stratification tools and treatment modalities. Results: BrS has a worldwide prevalence estimated between 1 in 2000 and 1 in 5000 persons. Genetic mutations, especially affecting heart sodium channels, provide an arrhythmogenic substrate resulting in distinctive ECG abnormalities. Diagnosis is driven by revised clinical criteria and electrophysiological results. Management involves the use of implanted cardioverter-defibrillators (ICDs) and medication. Recent findings have clarified genotype-phenotype connections and enhanced patient risk classification Conclusion: Brugada syndrome is a complicated cardiac illness needing standardized diagnostic techniques and specialized therapeutic options. Future research should concentrate on enhancing genetic screening, risk prediction models, and the development of tailored medicines to lower sudden cardiac death risk.